Predictors of iatrogenic splenic injury in radical gastrectomy for gastric cancer - Zhang, Xin; Wei, Ziran; Fu, Hongbing; Hu, Zunqi; Wang, Weijun; Yan, Ronglin (Frontiers in Oncology, 2024)
Background: Iatrogenic splenic injury (ISI) is a recognized complication in radical gastrectomy that may result in incidental splenectomy (IS).However, the predictors of such events remain largely unknown.Methods: Medical records of the patients who underwent radical gastrectomy at our institution between January 2015 and December 2022 were retrospectively reviewed. Potential predictors of ISI and IS were collected and analyzed by multivariate logistic regression. Results were reported as an odds ratio (OR) with 95% confidence intervals (CI).Results: A total of 2916 patients were included, of whom 211 patients (7.2%) suffered from ISI and 75 patients (2.6%) underwent IS.Multivariate analysis demonstrated that BMI ≥ 25 (OR: 3.198 (2.356-4.326), p<0.001), total gastrectomy (OR: 2.201 (1.601-3.025), p<0.001), and the existence of "criminal fold" (OR: 13.899(2.824-251.597), p=0.011) were independent predictive risk factors for ISI; whereas laparoscopic surgical approach (OR: 0.048 (0.007-0.172), p<0.001) was a protective factor for ISI. Moreover, the existence of "criminal fold" (OR: 15.745 (3.106-288.470), p=0.008) and BMI≥25 (OR: 2.498 (1.002-6.046), p=0.044) were identified as independent risk factors of ISI under laparoscopic gastrectomy. There was no association between sex, age, previous abdominal surgery, neoadjuvant therapy, outlet obstruction, tumor stage, nodal stage, and total lymph node retrieved and ISI.Conclusions: BMI≥25 and total gastrectomy can predict high risk of ISI during radical gastrectomy. Laparoscopic surgery is superior to open gastrectomy in lowing the risk of ISI.